Armed reproductives: evolution of the frontal gland in imagoes of Termitidae - Kutalová, Kateřina; Bourguignon, Thomas; Sillam-Dussès, David; Hanus, Robert; Roisin, Yves; Sobotník, Jan (Arthropod structure & development, 2013)
The frontal gland of termites is a structure without any equivalent among other animals. Although this gland is well known in soldiers, it received almost no attention in other castes. Recently, we described it in imagoes of Rhinotermitidae and Serritermitidae. In order to provide a complete picture of the evolution of this gland in termite imagoes, we studied it in additional 34 species of Termitidae, representing 7 of the 8 subfamilies. The frontal gland of these species is formed by class 1 secretory cells only, and occurs in two basic shapes: epithelial with reservoir in Foraminitermitinae and Macrotermitinae, and epithelial without reservoir in all other subfamilies. The size variability of the gland is high, not only among Termitidae subfamilies, but also within subfamilies. Our data suggest that the ancestral form of the frontal gland is epithelial with reservoir, as found in Rhinotermitidae, Serritermitidae, and basal Termitidae. The reduction of the reservoir occurred at least two times and the gland was lost two times independently: in Protermes sp. and in Microtermes toumodiensis (both Macrotermitinae).
Keywords: transmisní elektronová mikroskopie; Phylogeny; ženské pohlaví; zvířata; exokrinní žlázy; Biological Evolution; Male; Microscopy, Electron, Transmission; Animals; Female; Population Dynamics; mužské pohlaví; populační dynamika; fylogeneze; Exocrine Glands; biologická evoluce; Isoptera